THE FACTORS INFLUENCING SOCIAL ENTREPRENEURIAL INTENTION (SEI) AMONG GEN-Z IN MALAYSIA - Rodhi, Siti Asma Mohd Rosdi Mohd; Raja Abdullah, Raja Nazim; Yusuf, Robe’ah; Zainal Adnan, Ahmad Amri; Sabri, Siti Shalima; Tripalupi, Ramadhani Irma (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Social entrepreneurship has garnered heightened attention as a sustainable approach to tackling social and economic issues; yet engagement among youth remains comparatively low, especially in developing economies. This research investigates the factors influencing Social Entrepreneurial Intention (SEI) among Generation Z in Malaysia through an augmented TPB framework. The study specifically examines the impact of Attitude Toward Social Entrepreneurship (ATSE), Subjective Norms (SN), Perceived Behavioural Control (PBC), Social Innovation Orientation (SIO), Knowledge of Social Entrepreneurship (KSE), and Educational Support (ES) on Social Entrepreneurship Intention (SEI). A quantitative, cross-sectional approach was utilized, and data were gathered from 310 Malaysian Generation Z participants through a standardized questionnaire. The data were analysed with Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings demonstrate that Educational Support exerts the most substantial positive and statistically significant influence on SEI (β = 0.624, t = 8.085, p < 0.001), succeeded by Perceived Behavioural Control (β = 0.233, t = 3.686, p < 0.001) and Subjective Norms (β = 0.165, t = 2.678, p = 0.007). Conversely, ATSE (β = 0.040, p = 0.524), KSE (β = −0.012, p = 0.848), and SIO (β = −0.113, p = 0.070) do not demonstrate significant direct associations with SEI. The findings offer partial validation of the expanded Theory of Planned Behaviour paradigm and underscore the significant impact of institutional support, perceived capability, and social influence on the social entrepreneurial intentions of Generation Z. The study provides significant theoretical insights and practical consequences for educators and governments seeking to promote social entrepreneurship among youngsters.